Inter-sample contamination detection using mixture deconvolution comparison. (May 2019) - Taylor, Duncan; Rowe, Emily; Kruijver, Maarten; Abarno, Damien; Bright, Jo-Anne; Buckleton, John
Highlights: We trial a mixture to mixture comparison tool in a quality assurance context. All samples within eight extraction batches and four run batches were compared. Two mechanisms of potential sample to sample contamination were investigated. No instances of sample to sample contamination were identified. The potential for sample to sample intelligence gathering was explored. Abstract: A recent publication has provided the ability to compare two mixed DNA profiles and consider their probability of occurrence if they do, compared to if they do not, have a common contributor. This ability has applications to both quality assurance (to test for sample to sample contamination) and for intelligence gathering purposes (did the same unknown offender donate DNA to multiple samples). We use a mixture to mixture comparison tool to investigate the prevalence of sample to sample contamination that could occur from two laboratory mechanisms, one during DNA extraction and one during electrophoresis. By carrying out pairwise comparisons of all samples (deconvoluted using probabilistic genotyping software STRmix™) within extraction or run batches we identify any potential common DNA donors and investigate these with respect to their risk of contamination from the two proposed mechanisms. While not identifying any contamination, we inadvertently find a potential intelligence link between samples, showing the use of a mixture to mixture comparison tool for investigative purposes.